2022
DOI: 10.1111/coep.12570
|View full text |Cite
|
Sign up to set email alerts
|

The college admissions contribution to the labor market beauty premium

Abstract: We investigate the contribution of college admissions to the labor market beauty premium. We sampled 1800 social media profiles of students from universities ranked from 1 to 200 in China and the US. Chinese universities use standardized test scores for admissions. US universities use also extracurricular activities. Consistent with beauty‐blind admissions, alumni's beauty is uncorrelated with the rank of the school they attended in China. In the US, White men who attended high‐ranked schools are better lookin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…From an applied psychological point of view, attractiveness is also an important factor in social interactions, including college admissions and job applications ( Shtudiner, 2020 ; Ong, 2022 ; Ruffle et al, 2022 ; Shapir and Shtudiner, 2022 ). A number of studies have suggested that more attractive people are offer higher salaries in the job market and earn more on average, although there is no evidence that they perform better than colleagues ( Heilman and Saruwatari, 1979 ; Mobius and Rosenblat, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…From an applied psychological point of view, attractiveness is also an important factor in social interactions, including college admissions and job applications ( Shtudiner, 2020 ; Ong, 2022 ; Ruffle et al, 2022 ; Shapir and Shtudiner, 2022 ). A number of studies have suggested that more attractive people are offer higher salaries in the job market and earn more on average, although there is no evidence that they perform better than colleagues ( Heilman and Saruwatari, 1979 ; Mobius and Rosenblat, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Attractiveness has significant positive impacts on a professor’s promotion and career success ( Liu Y. et al, 2022 ). Attractive individuals may be favored in the college admissions process ( Ong, 2022 ) and get more fringe benefits at work ( Dilmaghani, 2020 ). As stated by Langlois et al (2000) : “beauty is more than just skin-deep” (p.404).…”
Section: Introductionmentioning
confidence: 99%
“…Facial attractiveness played a critical role in pain empathic responses ( Kopiś et al, 2020 ). Decades of research have proved the effect of “beauty is good,” ( Dion et al, 1972 ) which means that people will attribute more positive traits ( Shtudiner, 2020 ; Shtudiner and Klein, 2020 ; Ong, 2022 ) and generate more pro-social behaviors such as trust, cooperation and pain empathy to physically attractive people ( Chen et al, 2012 ; Balconi et al, 2020 ; Ch’ng, 2021 ). Some studies indicated that high facial attractiveness would elicit more empathetic responses than low facial attractiveness by using ERP or fMRI methods ( Jankowiak-Siuda et al, 2015 ; Balconi et al, 2020 ; Meng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%